User Experience Techniques Adopted by Brazilian Game Development Studios: An Exploratory Study - Felippe Fernandes da Silva; Matheus Henrique C. Leme; André F. Zanella; Guilherme Corredato Guerino; Renato Balancieri; Gislaine Camila Lapasini Leal (International Journal of Computer Games Technology)
Game development studios deal with numerous challenges to achieve the publication of games that are acclaimed by the public. The difficulties range from a simple choice of color for a particular object within the game to mechanics and narratives. In this way, user experience (UX) techniques provide a better perception of the player’s experience. UX techniques are consolidated in the context of software engineering industries and literature. However, few works in the literature (which will be presented in this work) address this knowledge and treat digital games as a specific type of software. In this sense, we aim to explore and present innovative approaches and best techniques adopted by game development studios to integrate UX into their processes. The research included the participation of 41 digital game development studios from all regions of Brazil, of which 31 were interviewed and 10 chose to participate via questionnaire. The analysis revealed that many participants work in small companies (up to five employees) and apply UX techniques intuitively without formal knowledge and justification for using them. Furthermore, we noticed that many studios are unclear about their techniques and confuse them with game design. However, most understand that UX is fundamental for designing a successful game with community support and buy-in. In addition, most of the justifications for not using UX techniques converged on a lack of knowledge. Finally, we developed a visual scheme to assist studios and future research, capable of consolidating the information extracted from participants about the UX techniques adopted, the benefits and challenges of applying them to the development process, the justifications for not adopting UX techniques (when not adopted), the test instruments implemented, and the UX dimensions evaluated by them.